Use of Nusinersen in type 1 Spinal Muscular Atrophy. Literature Review (Research, Society and Development, 2022)
Type 1 spinal muscular atrophy is a neurodegenerative disease, caused by a deletion or mutation of the SMN1 gene. There is currently only one drug approved for its treatment in Brazil, which is nusinersen. The present study aimed to carry out a literature review to review the effectiveness of nusinersen in the treatment of type 1 spinal muscular atrophy. As well as, talk about the clinical studies carried out and the advances in treatment in terms of gain in motor milestone, motor function, use of mechanical ventilation and treatment safety. At the nusinersen group, 22% of babies achieved full head control, 10% were able to roll over, 8% were able to sit up independently and 1% managed to stand up; at the control group, no baby reached these Marcos. Regarding motor function, the scale was used CHOP-INTEND, which showed a score greater than 40, was seen in none of 13 babies with two copies of the gene at baseline and increased for seven of 13 participants at last visit in the 12 mg group.Overall, the risk of death or the use of permanent assisted ventilation was 47% lower in the nusinersen group than in the control group. The use of nusinersen proved to be effective in gaining motor milestones and using assisted ventilation, and even greater survival. However, it is tied to the onset of symptoms and the number of copies of the SMN2 gene. As for motor force, no study has been able to prove the return of motor force in its excellence.